The Problem of Optimizing Social Media as a Means of Community Education - Wicaksono, Muhammad Bagus Adi; Tristiana, Enis; Ratnadewanti, Aldora Diasayu (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This study describes and examines the relevance of the use of Instagram Social Media as a means of educating the public about population administration and optimization efforts at the Surakarta City Population Administration and Civil Registration Office. The type of data used in this study is primary data obtained from observations and interviews and secondary data obtained through literature studies. The results of this study show that the use of Instagram Social Media at the Surakarta City Administration and Civil Registration Office as a means of educating the public about population administration is still not optimal. This is evidenced by the limited availability of human resources who manage Instagram Social Media this affects the educational content provided on social media and has an impact on the minimal benefits felt by the community. Based on the results of the study, efforts are needed to optimize the use of Instagram Social Media as a means of educating the public about population administration so that various information about population administration can be conveyed to all levels of society.